Oportunidades y desafíos para la Argentina en el mercado de Asia Oriental: Un estudio de impacto - CEI - Centro de Economía Internacional (Buenos Aires) (Centro de Economía Internacional (CEI), 2003)
– A region which harbors 30% of the world population - 1,700 million inhabitants - and produces 14% of the global economy, and that, in addition, shows the biggest commercial growth rates of the last two decades appears to be the inexorable fate for a country which needs to increase substantially its placement in the exporting world. In that case, East Asia offers a promising market for the Argentine products, both due to the size and dynamism of its economy and the match between its demand for imports and our potential for exports. Although this region is fully integrated to the international trade (it generates 24% of the world exports and 21% of the world imports), Argentina's commercial exchange with East Asia is clearly underexploited since it is hardly represented in 10.2% of our foreign sales and in 10.4% of our purchases. However, there are numerous commercial opportunities for our products in the region. Argentine products that have greater opportunity of increasing its sales in these countries have been identified, which can be divided into those products which are already sold there and those which have not yet entered, i.e. the unexploited opportunities. Among the first group, the Asian countries have made imports in the amount of 107 thousand million dollars, and Argentina has sold only 1,992 million out of these. The greatest opportunities occur in those items where there is a match between the Argentine export structure and the Asian countries' import structure: the food sector (oleaginous foodstuff, such as seeds, oil or flour, cereals, fish, and fruit), fuels, chemicals, metal manufactures (steel and aluminium), and leather. Out of these, those having the greater insertion are the oleaginous sector products, while a medium and low insertion can be found among leather and steel manufactures.
Keywords: 330; Internationale Wirtschaftsbeziehungen; Ostasien; Argentinien